Progress of non-small-cell lung cancer with ROS1 rearrangement - Yang, Xin; Tang, Zhe; Li, Jing; Jiang, Jizong; Liu, Yue (Frontiers in Molecular Biosciences, 2023)
ROS1 rearrangement is found in 0.9%–2.6% of people with non-small-cell lung cancers (NSCLCs). Tyrosine kinase inhibitors (TKIs) target ROS1 and can block tumor growth and provide clinical benefits to patients. This review summarizes the current knowledge on ROS1 rearrangements in NSCLCs, including the mechanisms of ROS1 oncogenicity, epidemiology of ROS1-positive tumors, methods for detecting rearrangements, molecular characteristics, therapeutic agents, and mechanisms of drug resistance.